Eksplorasi Etnomatematika pada Alat Permainan Tradisionaldan Kontribusinya Bagi Pendidikan di Sekolah Dasar - Lestari, Dini; Tisngati, Urip; Sugiyono, Sugiyono (Scholarly Journal of Elementary School, 2023)
The study aims to learn what mathematical concepts are found in traditional game tools (hula hoop, the tray, and the kite) and to learn the contribution of ethnomathematics to traditional game tools for elementary school education. It was a qualitative study using an ethnographic approach. Research subjects were 7 elementary school students (a 3rd class student, three 4th graders, and three 6th graders) in the village neighborhood of sirnoboyo and two elementary school teachers (a class 4 teacher and a class 5 teacher). Sampling technique used to determine student subjects. The data collection methods used observation, interviews, and documentation. Data analysis suggests that: 1) the traditional game hula hoop, the tray, and the kite were responsible for the mathematical concepts. The mathematical concept of the traditional game tool was line, Angle, point of view, and get up flat. 2) traditional game tools as hula hoop, bakiak, and kites have contributed as a source of mathematical learning at elementary school. 3) the character traditional game hula hoop, the bakiak, and the kite were self-sufficiency, confidence, teamwork, and unity.